Studies on the differences in uptake and utilization of soil potassium between different rice genotypes - WANG Wei-mu; YANG Xiao-e; WEI You-zhang; YE Zheng-qian; DIAO Wei-ping (浙江大学学报. 农业与生命科学版, 2005)
The differences between uptake and utilization of soil K by two lowland rice genotypes differed in the tolerance to low K were studied by rhizobox cultivation. The results showed that the growth of aerial part of Fujiandao, a rice genotype tolerant to low K, was not obviously affected by low K stress, but the dry root weight was a little promoted. When K supply was adequate, the depletion ratios of all soil K fractions in the rhizosphere of 81394, a genotype sensitive to low K, were more serious than those in the rhizophere of Fujiandao, which may be the result of rice genetic characteristics. Under low-K stress, the depletion ratios of the readily-available K and the exchangeable K in the rhizosphere (<2 mm) of Fujiandao were 96% and 84%, respectively, while it was 93.7% and 66%, respectively, in that of 81394. The depletion ratios of two K form in the soil at 10 mm from root surface of Fujiandao was still as high as 83% and 84%, respectively, but it was decreased to 53% and 44%, respectively, in 81394. There was no significant difference of readily-released K content between the rhizophere of Fujiandao and 81394. The average depletion ratio of slowly-released K in the rhizophere (<3 mm) of Fujiandao was 56.6%, which was significantly higher than that of 81394, 41.7%. More visible descending of soil pH in the rhizosphere of Fujiandao was found compared to that of 81394, which should be the result of the more proton secretion adapting to low-K stress, and the reason of reletively more rapid transformation of slowly-released K into available K promoted in the rhizosphere of Fujiandao than those of 81394.